Commodity risk assessment of Malus domestica plants from Ukraine. (11th November 2021) - ; Bragard, Claude; Dehnen‐Schmutz, Katharina; Gonthier, Paolo; Jacques, Marie‐Agnès; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; et al.
Abstract: The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as 'High risk plants, plant products and other objects'). This Scientific Opinion covers plant health risks posed by 1‐ to 3‐year‐old dormant grafted plants and rootstocks of Malus domestica imported from Ukraine, taking into account the available scientific information, including the technical information provided by Ukraine. All pests associated with the commodity were evaluated against specific criteria for their relevance for this opinion. Two quarantine pests ( Lopholeucaspis japonica and Tobacco ringspot virus), one protected zone quarantine pest ( Erwinia amylovora ) and one non‐regulated pest ( Eotetranychus prunicola ) that fulfilled all relevant criteria were selected for further evaluation. For Erwinia amylovora, for which special requirements are specified in Commission Implementing Regulation (EU) 2019/2072, Annex X, item 9, the fulfilment of these requirements was evaluated. Based on the information provided in the dossier, the specific requirements for Erwinia amylovora were not met. For the three remaining selected pests, the risk mitigation measures proposed in the technical dossier from Ukraine were evaluated taking into account the possible limiting factors. For the selected pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The degree of pest freedom varies among the pests evaluated, with Eotetranychus prunicola being the pest most frequently expected on the imported plants. The Expert Knowledge Elicitation indicated with 95% certainty that between 9, 912 and 10, 000 bundles (consisting of 50 plants each) per 10, 000 would be free from Eotetranychus prunicola .